Non-Invasive Wristwatch Microstrip Antenna Sebagai Pengukur Kadar Gula Dalam Darah Pada ISM (Industrial,Science,and Medical) Band - Nugraha, Wahid Nova; Rahayu, Yusnita; Praludi, Teguh (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Diabetes mellitus affects millions of people worldwide. At present, the technology used by people with diabetes for determining blood glucose concentration is an invasive method that requires a blood sample and is thus painful. Bloodless and painless technology to monitor blood glycaemic levels could improve the lives of diabetes patients. This paper presents the design of a Mikrostrip antenna which can be used for non-invasive blood glucose monitoring. The antenna works well atfrequency of 2.46 GHz. This frequency shift can be used to observe the change in blood's concentration, which will be used to estimate the concentration of glucose in the blood.Keywords: Mikrostrip Antenna, Return Loss, Non Invasive Method,Glucose Monitoring, ISM Band